2008
DOI: 10.1590/s0036-46652008000600003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological analysis of patients with HIV/AIDS admitted to a reference hospital in the northeast region of Brazil

Abstract: SUMMARYThe AIDS epidemic has become a worldwide phenomenon of enormous magnitude and extension, deeply transforming medical practices and public health initiatives. This retrospective survey aimed to analyze clinical and epidemiological characteristics of patients with HIV/AIDS admitted to the Institute of Tropical Diseases Natan Portella, Teresina, Piauí, Brazil, from January, 2001 through December, 2004. Of the 828 patients, 43% were from other states and 71.3% were men. Average patient age was 35.4 ± 11.5 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 25 publications
2
19
1
9
Order By: Relevance
“…27 and Hurissa et al 28 . Our mortality rates were lower than those reported in a study conducted in Belo Horizonte (15) (17%) but higher than those reported by Oliveira et al 32 (8.7%) and Soares et al 35 (7.5%). The mortality and recurrence rates reflect the importance of the early detection and treatment of HIV in patients with VL, in order initiate appropriate treatment and prevent mortality.…”
contrasting
confidence: 76%
“…27 and Hurissa et al 28 . Our mortality rates were lower than those reported in a study conducted in Belo Horizonte (15) (17%) but higher than those reported by Oliveira et al 32 (8.7%) and Soares et al 35 (7.5%). The mortality and recurrence rates reflect the importance of the early detection and treatment of HIV in patients with VL, in order initiate appropriate treatment and prevent mortality.…”
contrasting
confidence: 76%
“…Em um estudo prospectivo em ambulatório de referência em Belo Horizonte para pacientes com HIV/aids, também houve predomínio do sexo masculino, correspondendo a 68% dos estudados (10) . Em estudo retrospectivo realizado em um hospital de referência do nordeste para doenças tropicais, os indivíduos do sexo masculino corresponderam a 71,3% da população de pacientes versus 28,7 do sexo feminino (11) . Um estudo observacional descritivo seccional sobre aids e envelhecimento também mostrou predomínio do sexo masculino, com 75% dos casos, e essa prevalência se mostrou tanto entre o grupo etário mais jovem quanto entre o grupo mais velho (12) .…”
Section: Discussionunclassified
“…A prospective study in a reference clinic in the city of Belo Horizonte, State of Minas Gerais, also showed the prevalence of HIV/aids in male patients, corresponding to 68% (10) . A retrospective study conducted at a tropical diseases reference hospital in the Northeast region, showed that male individuals correspond to 71.3% versus 28.7% of female patients (11) . A descriptive observational sectional study on aids and aging also showed a predominance of males, 75% of cases, and that this prevalence was among both the younger and the older age groups (12) .…”
Section: Discussionmentioning
confidence: 99%